Rezension von: Byrd, Gary B., The Ratskeller Controversy and the Schwäbisch Hall City Council 1509-1512 - Wunder, Gerd (Württembergisch Franken, 1977)
Gary B. Byrd: The Ratskeller Controversy and the Schwäbisch Hall City Council 1509-1512. (Sixteenth Centuy Journal VI, 1,1975, S. 94-110).